Quantitative biostratigraphical ranges of some late Cenozoic species of the dinoflagellate genus Spiniferites and taxonomic considerations. (20th December 2018) - Londeix, Laurent
Abstract: A new quantitative biostratigraphical method, based on an 'index of stratigraphical abundance' (ISA), has been used to refine the stratigraphical range of 50 dinoflagellate cyst taxa. Most of these correspond to Quaternary representatives of Achomosphaera or Spiniferites . Some extinct taxa are also discussed when their morphology is close to that of recent species (e.g. Spiniferites lenzii, S. twistringiensis and S. pseudofurcatus ), as well as some species possibly related to the motile Gonyaulax spinifera complex. The ISAs of S. mirabilis and S. hyperacanthus are similar, as well as for S. elongatus and S. sphaericum . Although initially presumed as indicating morphotypes of a same taxon, it seems rather that the ISAs similarites must be interpreted as an indication of close ecological preferences. The emergence of forms of Spiniferites with low to absent septa appears relatively late (compared to the range of the genus), but the first occurrence of intergonal processes is relatively early, indicating that it is probably a character deeply rooted into the generic genome. The previously calculated phylogeny of some Gonyaulax motile cells shows a different tree pattern than the stratigraphical first appearance succession of their presumed cyst equivalents.